Pengaruh Karet Remah Terhadap Stabilitas Campuran Beraspal Laston AC-WC Menggunakan Metode Dry Mix: The Effect of Crumb Rubber on the Stability of Asphalt AC-WC Asphalt Mix Using the Dry Mix Method - Ulfah, Luthfiyyah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Roads must have the appropriate mix of thickness and design to protect the subgrade from damage and to accommodate the load pressure on the road. The purpose of this research is to investigate the effects of adding crumb rubber to the hot asphalt mixture of the Laston AC-WC type. The research was conducted in two stages, involving the creation of test specimens. In the first stage, the bitumen content of the specimens included 5%, 5.5%, 6%, 6.5%, and 7%. In the second stage, In the second stage, crumb rubber was added to the mixture at percentages: 0%, 5%, 10%, 15%, and 20%. The crumb rubber was mixed using the dry mix method. Several parameters were considered based on the results of the Marshall Test, in accordance with the General Highways specifications (VFA, VIM, VMA, Stability, Meltability and MQ). characteristics analysis aims to determine the impact of crumb rubber content on the elasticity, durability, and other properties of the asphalt mixture. Of all the variations of the hot mix asphalt type Laston AC-WC mixed with crumb rubber; the optimum level of crumb rubber mixture was obtained at 5% for the hot mix asphalt type Laston AC-WC. From the research results, when 5% crumb rubber was added to the asphalt mixture, the following values were obtained: 856.1 kg stability, 3.07 mm flow and 290.40 kg/mm MQ. In contrast, the stability value of hot asphalt concrete asphalt concrete type AC-WC with 5% asphalt has 813.7 kg stability, 3.03 mm flow and 268.30 kg/mm MQ.